2008
DOI: 10.1074/jbc.m803458200
|View full text |Cite
|
Sign up to set email alerts
|

Positive Versus Negative Modulation of Different Endogenous Chemokines for CC-chemokine Receptor 1 by Small Molecule Agonists through Allosteric Versus Orthosteric Binding

Abstract: 7 transmembrane-spanning (7TM) chemokine receptors having multiple endogenous ligands offer special opportunities to understand the molecular basis for allosteric mechanisms. Thus, CC-chemokine receptor 1 (CCR1) binds CC-chemokine 3 and 5 (CCL3 and CCL5) with K d values of 7.3 and 0.16 nM, respectively, as determined in homologous competition binding assays. However, CCL5 appears to have a >10,000-fold lower affinity in competition against 125 I-CCL3. Mutational mapping revealed that CCL3 and CCL5 both are str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(99 citation statements)
references
References 38 publications
8
91
0
Order By: Relevance
“…Position V:12, which protrudes right into the major binding pocket, is conserved as a small amino acid (Gly in 29% and Leu in 14%), and in some receptors, introduction of larger side chains abolishes receptor activity (Jensen et al, 2008). Despite this, we observed only a minor decrease (1.6-fold) for the substitution of Gly for Trp in V:12 (Table 1).…”
Section: Resultsmentioning
confidence: 48%
“…Position V:12, which protrudes right into the major binding pocket, is conserved as a small amino acid (Gly in 29% and Leu in 14%), and in some receptors, introduction of larger side chains abolishes receptor activity (Jensen et al, 2008). Despite this, we observed only a minor decrease (1.6-fold) for the substitution of Gly for Trp in V:12 (Table 1).…”
Section: Resultsmentioning
confidence: 48%
“…In this manner, a particular ligand-modulator-receptor complex may be capable of stabilizing a distinct conformation, and the effect of this modulation is unique to any given receptor and signaling pathway being studied, a phenomenon recently referred to as "functional selectivity" (Urban et al, 2007). The operational models illustrate that the effect of the allosteric ligand on the signaling output is entirely dependent on the probe with which it is interacting [i.e., probe dependence (Kenakin, 2005)], and this has been underscored recently with the same small-molecule allosteric agonist acting through the CCR1 receptor as either a positive or negative modulator depending upon the endogenous chemokine (probe) tested (Jensen et al, 2008). In the case of AMD3100, we have demonstrated that this ligand behaves differently against the same probe (CXCL12) at two different receptors (CXCR4 and CXCR7).…”
Section: Discussionmentioning
confidence: 99%
“…We used the metal ion chelator complexes bipyridine (Bip) and phenanthroline (Phe) in complex with zinc and copper (ZnBip, CuBip, ZnPhe, and CuPhe), which have been shown to activate CCR8 with micromolar potencies (31,33). These agonists bind to deeply located residues in the main binding pocket and are expected to be independent on extracellular receptor regions (34,35). The 7TM bridge was found to be important for small molecule-mediated activation, because alanine substitution of either Cys 106 or Cys 183 totally abolished activation, as exemplified by CuPhe (Fig.…”
Section: Resultsmentioning
confidence: 99%